Akkadian Documents from Ras Shamra - Speiser, E. A.
1. Ugaritic Akkadian — 2. The Hurrians in Ugarit and Alalaḫ — 3. The “dynastic” seal — 4. The našu-nadānu formula — 5. Taxes and contributions — 6. Ranks and occupations — 7. Miscellanea.